The contribution of the Gereformeerder Kerk to Afrikaner culture - Coetzee, J. H. (Koers, 1976)
The term culture is employed in this paper in the same comprehensive sense as in Van Til's work.l) Its fullest meaning is contained in the divine command to man to replenish the earth and to subdue it. God Almighty, by the strength of his Word, created what we usually refer to as nature in the broadest sense of the word. Man's calling is to "create", in a secondary sense, by unfolding the embryonics of nature. The Lord God created nature, man is bound by divine command to bring forth culture. The two specific and interrelated subjects then are the Gereformeerde Kerk and Afrikaans culture in mutual relation.